Cities, poverty and development - Gilbert, Alan; Gugler , Josef (Oxford, 1992)
Most people in developing countries live in cities, and by the end of the decade only the poorest cities in Africa and Asia will be predominantly rural. In this fully revised and updated edition, the authors describe the urbanization of poverty as well as reasons for migration to the city, urban survival skills, and the level of political involvement of migrants.
Keywords: "Urbanization, Developing countries"